Cascaded Interference and Multipath Suppression Method Using Array Antenna for GNSS Receiver - Jian Wu (IEEE Access, 2019)
The space-time adaptive processing method has been widely used for both narrowband and wideband interference suppression in GNSS receiver equipped with array antenna. However, the use of space-time filter may cause satellite signal distortion and lead to bias in pseudo-range measurement. In addition, multipath is one of the main error sources that will have a serious influence on the performance of the GNSS receiver. For precise applications, the error induced by space-time filter and multipath should be reduced. In this paper, a cascaded interference and multipath suppression method using an array antenna are proposed. In the first stage, the interference is suppressed by projecting the received array signal into the interference orthogonal subspace using subspace projection method. In the second stage, the directions of arrival (DOA) of the direct signal and the multipath signal are estimated using sparse recovery method. The DOA parameters enable the receiver to construct a space-time distortionless beamformer, which is used to null the multipath signals and maximize the signal-to-noise ratio. The method does not require the prior knowledge of the direction of the direct signal and achieves unbiased measurement while suppressing the interference and multipath. The simulation results demonstrate that the proposed method can achieve the interference and multipath suppression effectively, and have a distortionless response for the direct signal.